C/N, δ13C and δ15N in water column from Young Sound, NE Greenland - Ingrid Wiedmann; Maria Lund Paulsen; Johnna M Holding; Mie Hylstofte Sichlau Winding; Hans Roy; Mikael K Sejr; Katja Laufer-Meiser (PANGAEA, 2025)
This dataset contains measurements of nutrients in the water column of Young Sound (C/N, δ13C and δ15N). The samples for the measurements were taken in August 2019 with a small Niskin bottle rosette (12x1.2L) or by repeated casts of a 5L Niskin bottle.
In: Wiedmann, I et al. (2025): Impact of Different Types of Meltwater Runoff on Pelagic and Benthic Processes in Young Sound, NE Greenland [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986456